Feral pigeons as reservoirs for hazardous Chlamydophila psittaci strains with zoonotic potential - S. Asghari; H. Staji; H. R. Mohammadi; I. Ashrafi Tamai (Bulgarian Journal of Veterinary Medicine, 2023)
Chlamydophila psittaci is found in pigeons worldwide. The abundance of feral pigeons living in close contact with humans and livestock are considered a significant risk factor for human and farm animal infections. In Iran, little is known about the prevalence of C. psittaci and its genotypes in pigeons. The present cross-sectional study aimed to investigate the prevalence of C. psittaci in feral pigeons and to genotype the detected strains. In total, 384 fresh faecal samples were collected from different areas in Semnan (Iran). Out of all samples, 0.52% were positive for C. psittaci genome in Real Time-PCR. The partial ompA gene sequencing revealed that detected strains were identified as genotypes A and E. This is the first report of C. psittaci genotypes A and E in feral pigeons in Iran. The occurrence of C. psittaci genotypes A and E in the faeces of feral pigeons suggests potential environmental contamination with C. psittaci by pigeons and raise a public health concern.